A novel non genomic glucocorticoid signaling mediated by a membrane palmitoylated glucocorticoid receptor cross talks with GnRH in gonadotrope cells - Mohsen Ayrout (Nature Portfolio, 2017)
Abstract Glucocorticoid hormones (GC) are the main stress mediators associated with reproductive disorders. GC exert their effects through activation of the glucocorticoid receptor (GR) principally acting as a transcription factor. Beside well-established GR-mediated genomic actions, several lines of evidence suggest a role for rapid membrane-initiated GC signaling in gonadotrope cells triggered by a membrane-associated GR. Herein, we demonstrate the existence of a specific membrane-initiated GC signaling in LβT2 gonadotrope cells involving two related phosphoproteins: Ca2+/Calmodulin-dependent protein kinase II (CaMKII) and synapsin-I. Within 5 min, LβT2 cells treated with stress range of 10−7 M Corticosterone or a membrane impermeable-GC, BSA-conjugated corticosterone, exhibited a 2-fold increase in levels of phospho-CaMKII and phospho-synapsin-I. Biochemical approaches revealed that this rapid signaling is promoted by a palmitoylated GR. Importantly, GC significantly alter GnRH-induced CaMKII phosphorylation, consistent with a novel cross-talk between the GnRH receptor and GC. This negative effect of GC on GnRH signaling was further observed on LH release by mouse pituitary explants. Altogether, our work provides new findings in GC field by bringing novel understanding on how GR integrates plasma membrane, allowing GC membrane-initiated signaling that differs in presence of GnRH to disrupt GnRH-dependent signaling and LH secretion.